Timely assistance : evaluating the speed of Road Home grantmaking - Eden, Rick, 1954-; Boren, Patricia M., 1955-; RAND Gulf States Policy Institute (Organization); Rand Infrastructure, Safety, and Environment (Organization).; Rand Corporation; Louisiana Recovery Authority (Santa Monica, CA : RAND, 2008)
After hurricanes Katrina and Rita, the federal government made available $8.1 billion to help Louisiana reconstruct its housing stock. Louisiana's governor established the Road Home (RH) program to disburse the federal funds as grants to eligible homeowners. This documented briefing assesses whether the RH grantmaking process has performed in a timely fashion. Although some applications have been processed in a timely manner, the overall timeliness of the grantmaking process has not been consistently good and predictable. On average, homeowners had waited about 250 days for grants; many had waited well over a year. Many homeowners who applied early in the program had not received grants by mid-December 2007. For example, only about half of eligible applicants who applied in December 2006 had received grants a year later. To foster improvement in timeliness, the program should establish time goals for the total process and each major segment, both for the typical time and for variability.
Introduction -- The Road Home grantmaking process -- Evaluation of grantmaking timeliness -- Segment analyses -- Recommendations -- Appendix: Grant wait times, by ZIP code.
"A study by RAND Infrastructure, Safety, and Environment."
"RAND Gulf States Policy Institute."
Includes bibliographical references (p. 75).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Disaster relief -- Louisiana; Federal aid to housing -- Louisiana; Hurricane Katrina, 2005.